Identification Source of Variation on Regional Impact of Air Quality Pattern using Chemometric Techniques in Kuching, Sarawak - Liyana Zakri, Nur; Shakir Mohd Saudi, Ahmad; Juahir, Hafizan; Ekhwan Toriman, Mohd; Fahmy Abu, Izuddin; Muaz Mahmud, Muhammad; Feroz Khan, Md (International Journal of Engineering and Technology, 2018)
Air pollution has been considered a devastating environmental issue that can negatively impact human health and the environment. Kuching as one of the capital cities in Malaysia is also affected by air pollution and unsatisfactory air quality condition. Thus, the main objective is to identify the source of variation on regional impact of air quality pattern in Kuching, Sarawak. A seven-year (2009-2015) database was acquired from the Malaysia Department of Environment (DOE). The data were analysed using several Chemometric Techniques. The findings demonstrated strong positive correlation of Particulate Matter below than 10 microns (PM10) and API (r = 0.994). In addition, Principal Component Analysis (PCA) and Artificial Neural Network (ANN) revealed that Carbon Monoxide (CO), Ozone (O3) and PM10 were the most significant air pollutants in Kuching. Based on the results in the Statistical Process Chart (SPC) analysis, PM10, CO and O3 values exceeded the Control Limit (CL) of SPC. This study concluded that the application of air quality model in this study is relevant for mitigating action plan of air quality in Kuching, Sarawak, as it is of paramount importance to continuously monitor and manage the quality of air for the sustainability of the environment and human health.